Estudo teórico-experimental de uma caldeira de queimador poroso recíproco aplicado ao biogás - Souza, Luís Carlos Eduardo Oliveira de (2009)
The current Dissertation treats the theoretical and experimental studies about a non- conventional saturated steam boiler, in which a com bustion technology is employed, the “Filtration Combustion”, as basis for conception of its burner construction design. This combustion thermal system was studied by means of a prototype, in laboratory scale, specially developed for this research. It was prop erly instrumented in order to make it possible to monitor as well as the combustion proce ss as the energy extraction in the reaction zone. The objective of this investigation is to verify the effects of the Biogas obtained from the anaerobic digestion of the Green Coconut Skin Liquid (GCSL), on the boiler operation, concerning efficiency and polluta nt emissions, as well as the reaction stability. Biogas combustion is analyzed by numeri cal model simulations, which take in account the mass, energy (gas and solid phases) and species conservation equations. The model is structured with a flexible code in languag e FORTRAN, which includes equilibrium calculation performed through premixed combustion simulation software, the PREMIX, adapted to the combustion process and heat transfer in porous medium. The simulation allows the prediction of the temperature distribution profiles along the burner and the combustion products as function of two main operation parameters, the equivalence ratio and the air-fuel mixture flow vel ocity. Simulation results are compared with measurements in this analysis and some design aspects of the "Porous Burner Boiler” are discussed, which evidences its operational adva ntages in comparison to the conventional boilers, especially the high energy ex traction efficiency and low carbon and nitrogen oxides emission levels